WAYS OF TEACHING MUSIC THEORY IN MUSIC SCHOOLS - Aslanov Komil Akhrorovich (International Journal on Integrated Education, 2023)
The article examines the importance of interest in music at all stages of the development of an individual's society, the scientific-theoretical basis of educating young people in the spirit of national ideals, and its theoretical foundations in the process of music education and historical aspects, the Uzbek people that have reached us, pedagogical issues of the history of art and spirituality in the culture of music were discussed.